IL-3 Is a Marker of Encephalitogenic T Cells, but Not Essential for CNS Autoimmunity - Lee, Priscilla W.; Xin, Matthew K.; Pei, Wei; Yang, Yuhong; Lovett-Racke, Amy E. (Frontiers in Immunology, 2018)
Identifying molecules that are differentially expressed in encephalitogenic T cells is critical to the development of novel and specific therapies for multiple sclerosis (MS). In this study, IL-3 was identified as a molecule highly expressed in encephalitogenic Th1 and Th17 cells, but not in myelin-specific non-encephalitogenic Th1 and Th17 cells. However, B10.PL IL-3-deficient mice remained susceptible to experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. Furthermore, B10.PL myelin-specific T cell receptor transgenic IL-3−/− Th1 and Th17 cells were capable of transferring EAE to wild-type mice. Antibody neutralization of IL-3 produced by encephalitogenic Th1 and Th17 cells failed to alter their ability to transfer EAE. Thus, IL-3 is highly expressed in myelin-specific T cells capable of inducing EAE compared to activated, non-encephalitogenic myelin-specific T cells. However, loss of IL-3 in encephalitogenic T cells does not reduce their pathogenicity, indicating that IL-3 is a marker of encephalitogenic T cells, but not a critical element in their pathogenic capacity.